2019
DOI: 10.1186/s13578-019-0310-2
|View full text |Cite|
|
Sign up to set email alerts
|

IGFBP7 inhibits cell proliferation by suppressing AKT activity and cell cycle progression in thyroid carcinoma

Abstract: Background Thyroid cancer is the most common malignant endocrine tumor and is classified into papillary thyroid cancer (PTC), follicular thyroid cancer (FTC) and anaplastic thyroid cancer (ATC), which have substantially different characteristics. Insulin-like growth factor binding protein 7 (IGFBP7) has recently been recognized as a tumor suppressor in many cancer types. However, the expression pattern of IGFBP7 and its biological function in various types of thyroid carcinoma remain poorly unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…37 Low levels of phosphorylated AKT upregulated p21 cip1 and p27 kip1 leading to the induction of G1/ S-phase arrest in thyroid carcinoma cells. 38 Furthermore, downregulation of phosphorylated AKT inhibited proliferation and induced G1/S-phase arrest and apoptosis in glioma cells resulting to a significant reduction in the levels of Bcl-2 and cyclin D1. 39 In the present study, GA attenuated phosphorylation of PI3K and AKT, which was probably responsible for cell cycle arrest and apoptosis in GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…37 Low levels of phosphorylated AKT upregulated p21 cip1 and p27 kip1 leading to the induction of G1/ S-phase arrest in thyroid carcinoma cells. 38 Furthermore, downregulation of phosphorylated AKT inhibited proliferation and induced G1/S-phase arrest and apoptosis in glioma cells resulting to a significant reduction in the levels of Bcl-2 and cyclin D1. 39 In the present study, GA attenuated phosphorylation of PI3K and AKT, which was probably responsible for cell cycle arrest and apoptosis in GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…PTC accounted for 80% of TCs, and showed a better prognosis. However, patients with PDTC or ATC due to rapid progression and local or distant metastasis frequently led to worse prognosis [1][2][3][4]. In addition to the characteristics of rapid growth of tumor cells, metastasis has been one of the hallmarks in cancer, leading to tumor dissemination and aggressiveness [26].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the degree of differentiation, TC is categorized into three kinds, which include well-differentiated thyroid carcinomas such as papillary thyroid carcinoma (PTC) and follicular thyroid carcinoma (FTC), as well as poorly-differentiated thyroid carcinoma (PDTC) and anaplastic thyroid cancer (ATC). Of these, PDTC and ATC accounted for only 15% and less than 5% of all TC cases [2]. These types of thyroid carcinomas are responsible for more than half of all TC mortalities that occur due to early lymph node (LN) metastasis and invasion of neighboring organs [3].…”
Section: Introductionmentioning
confidence: 99%
“…As an important protein coding gene, studies of IGFBP7 have mainly focused on its suppressive role in various human malignancies, including thyroid carcinoma, cholangiocarcinoma, gastric cancer, hepatocellular carcinoma and breast cancer. 11,13,14 However, there are reports that the effects of IGFBP7 involve insulin resistance and the risk of metabolic syndrome, 33 which are considered closely related to the development of osteoporosis. [34][35][36] More importantly, recent studies have reported that IGFBP7 may play considerable roles in bone metabolism.…”
Section: Discussionmentioning
confidence: 99%